Current bycatch levels in Auckland Islands trawl fisheries unlikely to be driving New Zealand sea lion (Phocarctos hookeri)population decline. Issue 1 (28th October 2014) - Hamilton, Sheryl; Baker, G. Barry
Abstract: New Zealand sea lions are incidentally killed in trawl fisheries around the Auckland Islands with most mortality having been attributed to the Auckland Islands squid fishery. Fishery management measures include the establishment of a 12 nautical mile marine reserve around the Auckland Islands excluding all fishing within that range, the instigation of mortality limits that can trigger spatio‐temporal closures, and widespread use of a 'Sea Lion Excluder Device' (SLED) that allows sea lions to escape from a trawl net. Although there has been controversy regarding SLED efficacy, the evidence from numerous research trials and assessments is that SLEDs have contributed to reduced rates of sea lion bycatch in the Auckland Islands squid fishery. Population viability analysis (PVA) modelling, using VORTEX, of the Auckland Islands New Zealand sea lion population was undertaken to ascertain if the reported levels of bycatch of sea lions in trawl fisheries around the Auckland Islands are sustainable following substantial and effective mitigation to reduce bycatch, particularly in the Auckland Islands squid fishery. Modelling indicated slow population growth of the Auckland Islands New Zealand sea lion population with current bycatch estimates from all Auckland Islands trawl fisheries. Additional modelling seeking explanations for observed population declines over the last decade indicated that epizootic events that reduce pup production may have a greater impact on population growth, especially if these events are more frequent than previously assumed. Modelling results suggest that sea lion bycatch in the squid fishery and other trawl fisheries around the Auckland Islands is unlikely to be currently having a significant impact on the Auckland Islands New Zealand sea lion population. Therefore, resources should be directed towards other hypotheses for any continued sea lion population decline as well as continued refinement of mitigation techniques to reduce fisheries‐related mortality. Copyright © 2014 John Wiley & Sons, Ltd.